2009
DOI: 10.1063/1.3056197
|View full text |Cite
|
Sign up to set email alerts
|

UV excitation and radiationless deactivation of imidazole

Abstract: The vertical spectrum and the radiationless decay of imidazole have been investigated theoretically. Benchmark calculations were performed employing different methods and levels. Four different conical intersections were characterized and the reaction paths connecting the Franck-Condon region to them were computed. Two of the conical intersections show puckered structures while the other two show NH and ring dissociation patterns. The pipi( *)/S(0) N(1)-puckered conical intersection is connected to the planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 59 publications
4
98
1
Order By: Relevance
“…Table 2 reports selected results for the TZVP + mod basis set together with the root mean square deviation (RMSD) between the present theoretical results and the experimental results of Devine et al [39] using the fitted values reported in reference [27] In contrast to the results obtained for pyrrole, [23] the B3LYP functional is in better agreement with experimental values than the PBE0 functional. The functional with the largest fraction of Hartree-Fock (HF) exchange contribution (BHLYP) provides the worst results.…”
Section: Vertical Excitations and Ionization Potentialssupporting
confidence: 50%
See 3 more Smart Citations
“…Table 2 reports selected results for the TZVP + mod basis set together with the root mean square deviation (RMSD) between the present theoretical results and the experimental results of Devine et al [39] using the fitted values reported in reference [27] In contrast to the results obtained for pyrrole, [23] the B3LYP functional is in better agreement with experimental values than the PBE0 functional. The functional with the largest fraction of Hartree-Fock (HF) exchange contribution (BHLYP) provides the worst results.…”
Section: Vertical Excitations and Ionization Potentialssupporting
confidence: 50%
“…[33] Altogether, this means that TDDFT may not work well to describe the excited-state dynamics of some molecules and that excitedstate dynamics with TDDFT must always be preceded by an extensive check of the potential-energy surfaces. In the case of imidazole, the validity of TDDFT for studying its excited-state dynamics has been assured by the good comparison between TDDFT and ab initio multireference configuration interaction (MRCI) dynamics performed for pyrrole [23,34] and by comparative investigation of reaction pathways of imidazole computed with different methods, presented here and in reference [27]. However, as we shall discuss below, the TDDFT method proved to be inadequate for investigating crossing to the ground state, which is quite an important restriction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, such photo-induced ring-openings have now been explored theoretically in several heterocyclic systems, including furan, [117][118][119] pyrrole, 120 imidazole, 121 2-aminooxazole, 122 adenine, 123 spiropyran, 124,125 and -glucose.…”
Section: Isolated Molecule Dynamicsmentioning
confidence: 99%